A genomic and transcriptomic approach to investigate the blue pigment phenotype in Pseudomonas fluorescens - Andreani, Nadia Andrea; Carraro, Lisa; Martino, Maria Elena; Fondi, Marco; Fasolato, Luca; Miotto, Giovanni; Magro, Massimiliano; Vianello, Fabio; Cardazzo, Barbara (International journal of food microbiology, 2015)
Pseudomonas fluorescens is a well-known food spoiler, able to cause serious economic losses in the food industry due to its ability to produce many extracellular, and often thermostable, compounds. The most outstanding spoilage events involving P. fluorescens were blue discoloration of several food stuffs, mainly dairy products. The bacteria involved in such high-profile cases have been identified as belonging to a clearly distinct phylogenetic cluster of the P. fluorescens group. Although the blue pigment has recently been investigated in several studies, the biosynthetic pathway leading to the pigment formation, as well as its chemical nature, remain challenging and unsolved points. In the present paper, genomic and transcriptomic data of 4 P. fluorescens strains (2 blue-pigmenting strains and 2 non-pigmenting strains) were analyzed to evaluate the presence and the expression of blue strain-specific genes. In particular, the pangenome analysis showed the presence in the blue-pigmenting strains of two copies of genes involved in the tryptophan biosynthesis pathway (including trpABCDF). The global expression profiling of blue-pigmenting strains versus non-pigmenting strains showed a general up-regulation of genes involved in iron uptake and a down-regulation of genes involved in primary metabolism. Chromogenic reaction of the blue-pigmenting bacterial cells with Kovac's reagent indicated an indole-derivative as the precursor of the blue pigment. Finally, solubility tests and MALDI-TOF mass spectrometry analysis of the isolated pigment suggested that its molecular structure is very probably a hydrophobic indigo analog.
Keywords: Tryptophan; Up-Regulation; tryptofan; Gene Expression Profiling; genomika; potravinářská mikrobiologie; upregulace; spotřeba kyslíku; Oxygen Consumption; Pigments, Biological; transkriptom; Food Microbiology; down regulace; biologické pigmenty; Energy Metabolism; mléčné výrobky; fenotyp; Transcriptome; Comparative genomics and transcriptomics; Down-Regulation; energetický metabolismus; Pseudomonas fluorescens; Phenotype; Genomics; Oxidoreductases; fylogeneze; Dairy Products; Blue mozzarella; stanovení celkové genové exprese; Phylogeny; oxidoreduktasy